Clinical and cost‐effectiveness of two ways of delivering guided self‐help for people with an eating disorder: A multi‐arm randomized controlled trial. Issue 7 (17th May 2021) - Jenkins, Paul E.; Luck, Amy; Violato, Mara; Robinson, Clare; Fairburn, Christopher G.
Abstract: Objective: Increasing the availability and accessibility of evidence‐based treatments for eating disorders is an important goal. This study investigated the effectiveness and cost‐effectiveness of guided self‐help via face‐to‐face meetings (fGSH) and a more scalable method, providing support via email (eGSH). Method: A pragmatic, randomized controlled trial was conducted at three sites. Adults with binge‐eating disorders were randomized to fGSH, eGSH, or a waiting list condition, each lasting 12 weeks. The primary outcome variable for clinical effectiveness was overall severity of eating psychopathology and, for cost‐effectiveness, binge‐free days, with explorative analyses using symptom abstinence. Costs were estimated from both a partial societal and healthcare provider perspective. Results: Sixty participants were included in each condition. Both forms of GSH were superior to the control condition in reducing eating psychopathology (IRR = −1.32 [95% CI −1.77, −0.87], p  < .0001; IRR = −1.62 [95% CI −2.25, −1.00], p  < .0001) and binge eating. Attrition was higher in eGSH. Probabilities that fGSH and eGSH were cost‐effective compared with WL were 93% (99%) and 51% (79%), respectively, for a willingness to pay of £100 (£150) per additional binge‐free day. Discussion: Both forms of GSH were associated with clinical improvement and were likely to be cost‐effective compared with a waiting list condition. Provision of support via email is likely to be more convenient for many patients although the risk of non‐completion is greater.